Sex difference in composition of plaques of patients undergoing carotid endarterectomy - Rerkasem K. (2014)
Our study aimed to examine the hypothesis that women have more stable plaques (a lower proportion of lipid component and a higher proportion of fibrous tissue) compared to men. Plaque specimens of 141 consecutive carotid endarterectomy patients (60 females and 81 males) were studied. Medical histories were recorded and the plasma concentrations of cholesterol and inflammatory markers were measured. We found that plaques from females had significantly less lipid than those from males (p = .01): the mean percentage of plaque lipid for women and men was 47.8% and 58.2%, respectively. Plaques from females had more fibrous tissue than those from men (p = .02): the mean percentage of fibrous tissue for women and men was 38.8% and 29.8%, respectively. This study concluded that the histology of carotid artery plaques from women appears to be more stable than that of those from men. © BC Decker Inc. All rights reserved.